Low Cholesterol Level Linked to Reduced Semantic Fluency Performance and Reduced Gray Matter Volume in the Medial Temporal Lobe - Yang, Fan Nils; Stanford, Macdonell; Jiang, Xiong (Frontiers in Aging Neuroscience, 2020)
Hyperlipidemia has been proposed as a risk factor of dementia and cognitive decline. However, the findings of relationship between cholesterol level and cognitive/brain function have been inconsistent. Here using a well-controlled sample from the Parkinson's Progression Markers Initiative (PPMI), we investigated the probable non-linear relationship between plasma total cholesterol (TC) level, gray matter volume (GMv), and cognitive performance in 117 subjects (mean age, 61.5±8.9). Within the subjects with a desirable TC level (TC < 200 mg/dl), low TC levels were associated with reduced SF performance, as well as reduced GMv in three medial temporal regions (including bilateral anterior hippocampus). In contrast, no significant relationship between TC and cognition performance/GMv was found in individuals with a high cholesterol level (TC >= 200 mg/dl). Further ROI-based analysis showed that individuals with TC levels ranged from 100 to 160 mg/dl had the lowest GMv in the medial temporal regions. These findings suggest that low-normal TC level may be associated with reduced cognitive function and brain atrophy in regions implicated in neurodegenerative diseases, adding to a growing body of literature supporting low-normal cholesterol level (i.e., TC < 160 mg/dl) might have a detrimental effect on both cognition and brain health.